Hubungan Kesadaran Metakognisi dengan Hasil Belajar Mahasiswa Kedokteran di Fakultas Kedokteran UNTIRTA - Alifa, Fasya Husti; Abdullah, Rukman; Soemantri, Diantha (Universitas Sultan Ageng Tirtayasa, 2024)
Metacognitive awareness is a high-level thinking that involves active control over the cognitive processes involved in learning, consisting of two components, namely cognitive knowledge and cognitive regulation. In this study the aim was to assess the relationship between the metacognitive awareness component and student learning outcomes. This study involved 165 medical student respondents at Sultan Ageng Tirtayasa University. The results of the study found that the components of cognitive knowledge, namely declarative (p = 0.410), procedural (p = 0.187), and conditional (p = 0.927) did not significantly influence the learning outcomes of medical students (p > 0.05). In the components of cognition regulation, namely planning (p = 0.221), information management strategies (p = 0.514), understanding monitoring (p= 0.996), and evaluation (p = 0.873) did not significantly influence student learning outcomes. While the correction strategy has a significant relationship with learning outcomes (p = 0.01). In the analysis of the total metacognitive awareness score on learning outcomes, it was found that there was no significant relationship (p = 0.510). This means that there is no significant relationship between metacognitive awareness and learning outcomes of medical students at Sultan Ageng Tirtayasa University, both in the components of cognitive knowledge and cognitive regulation.